Pathogenic ATM Mutations in Cancer and a Genetic Basis for Radiotherapeutic Efficacy. Issue 3 (29th July 2020) - Pitter, Kenneth L; Casey, Dana L; Lu, Yue C; Hannum, Margaret; Zhang, Zhigang; Song, Xinmao; Pecorari, Isabella; McMillan, Biko; Ma, Jennifer; Samstein, Robert M; Pei, Isaac X; Khan, Atif J; et al.
Abstract: Background: Radiation therapy is one of the most commonly used cancer therapeutics but genetic determinants of clinical benefit are poorly characterized. Pathogenic germline variants in ATM are known to cause ataxia-telangiectasia, a rare hereditary syndrome notable for marked radiosensitivity. In contrast, somatic inactivation of ATM is a common event in a wide variety of cancers, but its clinical actionability remains obscure. Methods: We analyzed 20 107 consecutively treated advanced cancer patients who underwent targeted genomic sequencing as part of an institutional genomic profiling initiative and identified 1085 harboring a somatic or germline ATM mutation, including 357 who received radiotherapy (RT). Outcomes of irradiated tumors harboring ATM loss-of-function (LoF) mutations were compared with those harboring variants of unknown significance. All statistical tests were 2-sided. Results: Among 357 pan-cancer patients who received 727 courses of RT, genetic inactivation of ATM was associated with improved radiotherapeutic efficacy. The 2-year cumulative incidence of irradiated tumor progression was 13.2% vs 27.5% for tumors harboring an ATM LoF vs variant of unknown significance allele, respectively (hazard ratio [HR] = 0.51, 95% confidence interval [CI] = 0.34 to 0.77, P = .001). The greatest clinical benefit was seen in tumors harboring biallelic ATM inactivation (HR = 0.19, 95% CI = 0.06 to 0.60, P = .005), with statistically significant benefit also observed in tumors with monoallelic ATM inactivation (HR = 0.57, 95% CI = 0.35 to 0.92, P = .02). Notably, ATM LoF was highly predictive of outcome in TP53 wild-type tumors but not among TP53 -mutant tumors. Conclusions: We demonstrate that somatic ATM inactivation is associated with markedly improved tumor control following RT. The identification of a radio-sensitive tumor phenotype across multiple cancer types offers potential clinical opportunities for genomically guided RT.